2021
DOI: 10.1038/s41419-021-04169-7
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the catalytic -dependent and -independent roles of METTL3 in sustaining aberrant translation in chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm caused by the presence of tyrosine kinase BCR-ABL1 fusion protein, which deregulate transcription and mRNA translation. Tyrosine kinase inhibitors (TKIs) are the first-choice treatment. However, resistance to TKIs remains a challenge to cure CML patients. Here, we reveal that the m6A methyltransferase complex METTL3/METTL14 is upregulated in CML patients and that is required for proliferation of primary CML cells and CML cell lines sensitive and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…discovered that METTL3 is a novel oncogene in CML and potentially a therapeutic target for TKI-resistant CML. The m6A methyltransferase complex METTL3 / METTL14 and METTL3 is upregulated in primary CML patients, and its downregulation significantly impairs the proliferation of both primary CML cells and TKI-sensitive and TKI-resistant CML cells ( 60 ). Silencing METTL3 in K562 cells and the TKI imatinib mesylate-resistant K562 cell line (K562r), they found that METTL3 affects the growth and viability of CML cells directly and indirectly.…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
See 2 more Smart Citations
“…discovered that METTL3 is a novel oncogene in CML and potentially a therapeutic target for TKI-resistant CML. The m6A methyltransferase complex METTL3 / METTL14 and METTL3 is upregulated in primary CML patients, and its downregulation significantly impairs the proliferation of both primary CML cells and TKI-sensitive and TKI-resistant CML cells ( 60 ). Silencing METTL3 in K562 cells and the TKI imatinib mesylate-resistant K562 cell line (K562r), they found that METTL3 affects the growth and viability of CML cells directly and indirectly.…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
“…MYC, as a transcriptional activator, is notably affected by METTL3 in CML cells, including the protein, mRNA, and premRNA levels. METTL3 knockdown strongly reduced MYC expression at multiple levels in CML, which consequently regulated the genes associated with RNA metabolism ( 60 ). Moreover, they found that the PES1 protein was potentially involved in blocking the cell cycle in G1 phase after METTL3 knockdown in CML cells ( 60 ).…”
Section: The Biological Function Of Mettl3mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it has been reported that METTL3, an RNA m 6 A modifier, is also involved in the mechanism of CML development [ 130 ]. Specifically, Ianniello et al [ 130 ] identified that the m 6 A methyltransferase complex METTL3/METTL14 is highly expressed in CML patients and is essential to maintain the proliferation of primary CML cells and CML cell lines that are sensitive or resistant to tyrosine kinase inhibitors (TKIs) (e.g., imatinib). Notably, it has been reported that aberrant translation is thought to be one of the mechanisms that mediate BCR/ABL transformation and maintain the leukemic phenotype of CML cells [ 159 , 160 ].…”
Section: M 6 a Methylation Modifications And Hematological Malignanciesmentioning
confidence: 99%
“…METTL3 in human tissue is highly expressed and conserved, especially in the testes. Recent studies reported that METTL3 is significantly highly expressed in chronic myeloid leukemia ( Ianniello et al, 2021 ), thymic epithelial tumors ( Iaiza et al, 2021 ), esophageal cancer ( Han et al, 2021 ), and prostate cancer ( Chen et al, 2021b ), suggesting a close relationship with malignant tumor development. Previous studies also suggested that METTL3 is significantly up-regulated in BC.…”
Section: M6a Roles and Mechanisms In Bcmentioning
confidence: 99%